2014
DOI: 10.1586/14737175.2014.874286
|View full text |Cite
|
Sign up to set email alerts
|

Use of coercive measures in mental health practice and its impact on outcome: a critical review

Abstract: Although coercive measures have always been part of the psychiatric armamentarium, the ethical dilemma between the use of a "therapeutic" coercion and the loss of patients' dignity is one of the major controversial issues in mental health research and practice. The aims of the present review are to explore the existing literature on predictors of use of coercive measures and to explore the relationship between coercive measures and patient outcome. A literature search was conducted using MEDLINE, PsychyINFO, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 73 publications
3
76
0
3
Order By: Relevance
“…Looking at the international literature, in agreement with our results, in UK variations in involuntary admissions resulted related to the availability of approved social workers (Huxley & Kerfoot, 1993). However, a deeper analysis and further studies are needed to better explain this result, possibly with the inclusion of relevant staff-related factors such as attitudes and thoughts (Husum et al 2010;Luciano et al 2014). In Italy, the role of social workers is not strictly connected to involuntary admission procedures, as only the medical doctor assesses patients for involuntary admission criteria.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Looking at the international literature, in agreement with our results, in UK variations in involuntary admissions resulted related to the availability of approved social workers (Huxley & Kerfoot, 1993). However, a deeper analysis and further studies are needed to better explain this result, possibly with the inclusion of relevant staff-related factors such as attitudes and thoughts (Husum et al 2010;Luciano et al 2014). In Italy, the role of social workers is not strictly connected to involuntary admission procedures, as only the medical doctor assesses patients for involuntary admission criteria.…”
Section: Discussionsupporting
confidence: 87%
“…However, looking at staff provision, it seems that the amount of some professional figures affected the number of involuntary admissions, as already suggested for restraint practice (Bowers et al 2012;Luciano et al 2014). However, looking at staff provision, it seems that the amount of some professional figures affected the number of involuntary admissions, as already suggested for restraint practice (Bowers et al 2012;Luciano et al 2014).…”
Section: Discussionmentioning
confidence: 80%
“…Despite the widespread use of coercive measures, however, there is a remarkable lack of empirical evidence as to their association with treatment outcomes [1, 2]. A recent review of the literature [3] found only 13 studies on the relationship between coercive measures and treatment outcomes, and reported mixed findings, with the quality of all the studies rated as poor.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, levels of perceived coercion tend to reduce over time and improvements in functioning and psychotic symptoms are associated with reduced perceived coercion (Fiorillo et al, 2012). However, the longer term outcomes for these voluntarily admitted service users with high levels of perceived coercion ('the coerced voluntary') is unknown (Luciano et al, 2014). It is a controversial issue, as if individuals who require admission are persuaded or pressured into accepting a voluntary hospital admission, it could mean being 'spared' an involuntary admission.…”
Section: Introductionmentioning
confidence: 99%